PENERAPAN PEMBELAJARAN KOOPERATIF TIPE NHT UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 1 WANCI - Jaya, Zulham (FMIPA UNIVERSITAS NEGERI MALANG, 2017)
Based on the results of preliminary observations on the fourth grade SDN 1 Wanci obtained mathematics student learning outcomes is low, due to their lessons in class tersbut still conventional, so that students are less motivated and active in learning. That makes researchers made repairs learning process by conducting action research class at the school. This study aims to boost student learning outcomes in the material properties of integer arithmetic operations by implementing cooperative learning NHT. This research is a classroom action research (action research class room). The subjects were fifth grade students of SD Negeri 1 Wanci totaling 28 people, consisting of 16 male students and 12 female students. This study gives a chance in two cycles, each cycle consisting of two meetings. The learning process in every meeting in this study, conducted in accordance with the steps of cooperative learning NHT namely (1) the stage of group formation and numbering, (2) asking questions, (3) thinking together, and (4) the stage to answer questions. After going through two cycles of the learning process then, it can be stated implementation of cooperative learning NHT could improve the results of students mathematics learning in the material properties of arithmetic operations of integers class V SD Negeri 1 Wanci, with the percentage of the acquisition value of the test results on silus 1 by 75% or No 21 students who scored above the minimum completeness criteria, and a 21% increase in cycle 2 which becomes a 96% or there were 27 students who were able to scored above the minimum completeness criteria.